2020
DOI: 10.1590/2238-38752020v10213
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Mobility, Expectations and Attitudes Towards Inequality in Brazil

Abstract: After the end of the political and economic cycle that gave rise to the phenomenon that became known as the Brazilian new middle class, in this article we argue that this reading was not limited to verifying the increase in income and consume power of thousands of families, but also framed it within a broader narrative that has hindered the sociological investigation of the phenomenon. Thus, our first objective is to develop, with the support of empirical data from the National Household Sample Survey (PNAD-IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…Impermanence discourses uphold discontinuities in work and, by extension, personal lives in globalized markets. Impermanence has been shown to manifest in low job stability, part-time jobs, informal sector work, ambiguities about class distributions and opportunities for social and income mobility (Scalon et al, 2021), as well as meanings of class regarding inequalities and racial injustices (Lustig et al, 2020;Salata & Scalon, 2020), and myths of meritocracy (Wayne & Cabral, 2021). Impermanence promotes workers' autonomy as means of dealing with discontinuities while also affording opportunities for more fluid work arrangements and pursuit of new experiences throughout careers (Kuhn et al, 2008).…”
Section: White-collar Workers In Brazilmentioning
confidence: 99%
See 2 more Smart Citations
“…Impermanence discourses uphold discontinuities in work and, by extension, personal lives in globalized markets. Impermanence has been shown to manifest in low job stability, part-time jobs, informal sector work, ambiguities about class distributions and opportunities for social and income mobility (Scalon et al, 2021), as well as meanings of class regarding inequalities and racial injustices (Lustig et al, 2020;Salata & Scalon, 2020), and myths of meritocracy (Wayne & Cabral, 2021). Impermanence promotes workers' autonomy as means of dealing with discontinuities while also affording opportunities for more fluid work arrangements and pursuit of new experiences throughout careers (Kuhn et al, 2008).…”
Section: White-collar Workers In Brazilmentioning
confidence: 99%
“…The 2000s saw the rise of the Brazilian middle class. Analyses pointed to lower unemployment, more formal economy and white-collar work, increased income and education, and greater consumption (e.g., mobile phones, washing machines; Salata & Scalon, 2020). However, the rise of the middle class is contested.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…mídia consumo, são paulo v. 19, n. 55, p. 312-332, mai./ago. 2022 micaela diaz rosaenz 323 y prácticas de consumo y del uso del crédito, financiamiento y el creciente proceso de endeudamiento (BARROS; OLIVEIRA, 2014;RANGEL, 2012;SBICCA et al, 2012;MATTOSO;SILVA, 2009;MOTA GUEDES, 2006; entre muchos otros). Si la movilidad social ascendente del primer decenio del 2000 motivó una gran producción académica con eje en la relación entre política y consumo, el fin del ciclo de prosperidad económica y los cambios políticos, corrieron el foco de interés.…”
Section: El Nuevo Mileno Como Bisagraunclassified
“…These factors include financial, physical, and geographical hurdles and lack of encouragement to pursue higher education. Since the beginning of the present century, most of the studies have identified several socioeconomic factors related to the mobility of households, such as education, occupation, and income but fail to bring up a clear picture related to the structural changes in society (Salata & Scalon, 2020).…”
Section: Introductionmentioning
confidence: 99%